Invariants of a Cartesian tensor of rank 3 - Ahmad, F. (Archives of Mechanics, 2011)
General methods are applied to find complete sets of invariants of a tensor of rank 3. When the results are specialized to the piezoelectric tensor, it is found that the tensor has no linear invariant. Also under SO(2), as well as SO(3), the piezoelectric tensor has five quadratic invariants. The sets of invariants are complete.